HLA-B*5701 typing: evaluation of an allele-specific polymerase chain reaction melting assay - Hammond, E.; Cyril; Nolan, D.; Mallal, S. (Blackwell Munksgaard, 2007)
Inheritance of HLA-B*5701 is a strong predictor of a hypersensitivity reaction to the anti-HIV drug abacavir. The identification of susceptible individuals prior to the institution of abacavir therapy is therefore of clinical importance and has generated demand for a simple and rapid diagnostic test for carriage of HLA-B*5701. In this study, we describe the development of such a method based on allele-specific polymerase chain reaction (AS-PCR) and melting curve analysis. Ninety-six patient samples including 36 HLA-B*5701-positive samples and 60 HLA-B*5701-negative samples were analysed. Compared with sequence-based typing, this method had 100% sensitivity and specificity for the HLA-B*5701 allele. In conclusion, the AS-PCR/melting curve approach minimises post-polymerase chain reaction handling processing and provides an attractive alternative to currently described AS-PCR methods.